PENGARUH KONSELING TERHADAP STATUS PEMAKAIAN KONTRASEPSI DAN JENIS KONTRASEPSI PADA IBU NIFAS - Ridha Wahyuni (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Quality interaction or counseling between clients and providers (medical personnel), especially midwives, is one of the most decisive indicators for the success of family planning programs in Indonesia. Clients who get counseling well will tend to choose contraception correctly and precisely. The purpose of this study was to determine the effect of counseling on contraceptive usage status and type of contraception in postpartum mothers. This study is a quantitative analytical study and analyzed using Mann Whitney's test. The number of respondents was 36 people by dividing the intervention group by 18 respondents and the control group by 18 respondents. Obtained counseling effect test results with contraceptive use status in postpartum mothers with Asymp values. Sig. (2-tailed) 0.78> 0.05 and the results of the counseling effect test on the selection of contraception types in postpartum mothers with Asymp values. Sig. (2-tailed) 0.014 <0.05. The conclusions in this study were that there was no effect of counseling on contraceptive use status in postpartum mothers and there was an effect of counseling on the selection of contraception in postpartum mothers.